COMPARATIVE EFFICACY AND SAFETY OF HYPOLIPIDEMIC THERAPY WITH GENERIC AND ORIGINAL MEDICINAL PRODUCTS OF SIMVASTATIN - E. I. Tarlovskaya; Yu. A. Balandina; I. E. Sapozhnikova; N. S. Maksimchuk (Столичная издательская компания, 2016)
Aim. To compare efficacy , safety and pharmacoeconomical characteristics of generic and original medicinal products of simvastatin in achievement of cholesterol and low density lipoprotein target levels. Material and methods. 38 patients with arterial hypertension accompanied by type 2 diabetes with dyslipidemia were included into the study. They had no clinically obvious ischemic heart disease and did not receive hypolipidemic pharmacotherapy for a month before the study start. The patients were randomized into group A or group B. Patients of group A (n=18) received original simvastatin, patients of group B (n=20) received generic simvastatin. Initial simvastatin dose was 20 mg daily. Lipid plasma profile, liver enzymes, creatine phosphokinase were evaluated every 4 weeks. Cost-effectiveness ratio was calculated. Results. 11 patients (61%) in group A and only 5 patients (25%) in group B (χ2=5.05; р<0.05) achieved cholesterol target level with simvastatin in dose of 20 mg daily in 3 months of the treatment. Creatine phosphokinase blood level did not increase significantly. Achievement of cholesterol target level cost 814 and 952 RUB per patient in groups A and B, respectively , in 1 month of simvastatin treatment. These costs were 643 and 417 RUB per patient in groups A and B, respectively , in 3 months of treatment. Conclusion. The original simvastatin in comparison with generic one has advantages in hypolipidemic effect. Safety profile is similar for both medications. Original simvastatin therapy has lower cost than this for generic simvastatin therapy in achievement of cholesterol target level in 1 month of treatment. In 3 months the cost of treatment per patient is 227 RUB higher for original medication in comparison with this for generic medication.